Distribution Pattern of Riverbank Against Flood Inundation Based on Remote Sensing in Martapura Banjar Regency, South Kalimantan, Indonesia - Irawan, Vita; Hadibasyir, Hamim Zaky; Faizal, Rahmad (Universitas Muhammadiyah Surakarta, 2024)
Purpose: This research aims to conduct an in-depth analysis of settlement patterns along riverbanks and identify possible relationships between these settlement patterns and flood inundation. By focusing on remote sensing, spatial data to provide a holistic understanding of settlement dynamics and flood risk. Methodology: This research method uses the nearest neighbor approach, also commonly referred to as Average Nearest Neighbor (ANN). The data is analyzed based on the settlement distribution pattern that follows the river network. The role of remote sensing in the study of settlement distribution is crucial, especially in acquiring spatial data about the existence of settlements and the condition of the area at that time. Results: The results of this study show that the distribution pattern in parts of Martapura Sub-district indicates that building points are located along the river network, leading to an increasing concentration of buildings on the riverbanks. The impact of this distribution pattern is that the riverbanks become slums, which can result in tidal flooding.